One teacher, many grades: Foundation Phase teachers’ experiences in multigrade classroom management - Qangule, Tabisile; Letuma, Motsekiso Calvin (Frontiers in Education, 2025)
BackgroundMultigrade classrooms in the Foundation Phase present unique teaching and behavioural management challenges. These settings require innovative and consistent classroom management strategies to ensure effective learning.ObjectiveThis study explored how Foundation Phase teachers perceive and manage multigrade classrooms.MethodsThe study adopted an interpretive paradigm and employed a qualitative approach within a multiple case study design. It was grounded in Self-Efficacy Theory and the Alternatives to Establishing a Conducive Learning Environment (AECLE) model. Purposive sampling was used to select three schools, and five Foundation Phase teachers teaching in multigrade settings. Data was collected through semi-structured interviews and document analysis. Thematic analysis was used to interpret the data.ResultsThe findings revealed that teachers perceive multigrade classroom management as complex and demanding, primarily due to limited training, insufficient policy guidelines, and behavioural challenges associated with learner diversity. These conditions undermined teachers’ self-efficacy. Nonetheless, teachers applied adaptive strategies, such as rule-setting, modelling, reinforcement, learner movement, relationship-building, and grade splitting, that reflected emerging situational efficacy. However, inconsistent implementation of these strategies highlighted the absence of systematic professional development and institutional support tailored to multigrade contexts.ConclusionThe study concludes that improving multigrade classroom management requires professional development that directly addresses the unique pedagogical and behavioural challenges of teaching across grades. Strengthening teacher efficacy through structured, context-specific training could foster consistent application of management strategies and reduce reliance on fragmented, individual adaptations.